1)Given

un+1=7−2un

u2=5

Determine u1

Let us evaluate the recurrence relation un+1=7-2un at n=1 u2=7-2u1

Since u2=5 has been given: 5=7-2u1

Subtract 7 from each side: 5-7=7-2u1-7

Combine like terms: -2=-2u1

Divide each side by -2: \(-2/-2=-2u1/-2\)

Evaluate: 1=u1

Thus we then obtained u1=1

2)Determine u0

Let us evaluate the recurrence relation un+1=7-2un at n=0 u1=7-2u0

Since u2=5 has been given: 1=7-2u0

Subtract 7 from each side: 1-7=7-2u0-7

Combine like terms: -6=-2u0

Divide each side by -2: \(-6/-2=-2u0/-2\)

Evaluate: 3=u0

Thus we then obtained u0=3.

un+1=7−2un

u2=5

Determine u1

Let us evaluate the recurrence relation un+1=7-2un at n=1 u2=7-2u1

Since u2=5 has been given: 5=7-2u1

Subtract 7 from each side: 5-7=7-2u1-7

Combine like terms: -2=-2u1

Divide each side by -2: \(-2/-2=-2u1/-2\)

Evaluate: 1=u1

Thus we then obtained u1=1

2)Determine u0

Let us evaluate the recurrence relation un+1=7-2un at n=0 u1=7-2u0

Since u2=5 has been given: 1=7-2u0

Subtract 7 from each side: 1-7=7-2u0-7

Combine like terms: -6=-2u0

Divide each side by -2: \(-6/-2=-2u0/-2\)

Evaluate: 3=u0

Thus we then obtained u0=3.